2002
DOI: 10.1152/japplphysiol.00965.2001
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine elevates pulmonary vascular resistance in humans: potential for involvement of HIF-1

Abstract: Balanos, George M., Keith L. Dorrington, and Peter A. Robbins. Desferrioxamine elevates pulmonary vascular resistance in humans: potential for involvement of HIF-1. J Appl Physiol 92: 2501-2507, 2002. First published February 15, 2002 10.1152/japplphysiol.00965.2001.-Hypoxia-inducible factor (HIF)-1 is stabilized by hypoxia and iron chelation. We hypothesized that HIF-1 might be involved in pulmonary vascular regulation and that infusion of desferrioxamine over 8 h would consequently mimic hypoxia and elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 22 publications
3
52
0
3
Order By: Relevance
“…For data from animal experiments, hypoxic pulmonary vasoconstriction has been modeled as a sigmoidal function of PA O 2 , in which the sensitivity of the vascular response increases as PA O 2 decreases from ϳ100 Torr toward ϳ30 Torr (13). If the human response is similar in this respect, it is to be anticipated that the sensitivity of the pulmonary vascular response to hypoxia in the PA O 2 range of 80-140 Torr given for the normal erect lung (24) would be considerably less that the value of the 0.3 Torr change in ⌬P max per Torr change in PA O 2 , which is the average over the range of 50-100 Torr in our previous study (2). In contrast to this probably weak vascular response to hypoxia within the physiological range of PA O 2 in the healthy lung, the results presented here show a vigorous response to changes in PA CO 2 within the physiological range.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…For data from animal experiments, hypoxic pulmonary vasoconstriction has been modeled as a sigmoidal function of PA O 2 , in which the sensitivity of the vascular response increases as PA O 2 decreases from ϳ100 Torr toward ϳ30 Torr (13). If the human response is similar in this respect, it is to be anticipated that the sensitivity of the pulmonary vascular response to hypoxia in the PA O 2 range of 80-140 Torr given for the normal erect lung (24) would be considerably less that the value of the 0.3 Torr change in ⌬P max per Torr change in PA O 2 , which is the average over the range of 50-100 Torr in our previous study (2). In contrast to this probably weak vascular response to hypoxia within the physiological range of PA O 2 in the healthy lung, the results presented here show a vigorous response to changes in PA CO 2 within the physiological range.…”
Section: Discussionmentioning
confidence: 76%
“…Because ⌬Pmax is a measure of the difference between systolic pressure in the right ventricle and the fairly constant pressure in the right atrium, it can be used as an index of PVR. Indeed, we have recently argued that it may be a more direct indicator of smooth muscle activity in the pulmonary arteries than PVR itself (2). A standard technique was used for measuring ⌬P max (20).…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…He also reported that infusion of the iron chelator desferrioxamine results in enhanced pulmonary vascular responses to hypoxia in normal volunteers (44).…”
Section: Respiratory Diseasementioning
confidence: 97%